Geographical Appraisal of Gender Disparity and Progress in Literacy of Haryana, India - Manju Sharma; Sandeep Kumar (Faculty of Geography, Universitas Gadjah Mada, 2020)
The present research relates to the northern state of Haryana in India and to find out the objective of advancement and the existing gender gap in literacy with identification of responsible factors, the study uses the secondary data obtained from different censuses of India, National Crime Record Bureau and various other related sources. The disparity index is calculated to examine the gender gap in literacy whereas the correlation coefficient is used to ascertain its relationship with major determinants. Though the country and the state have achieved a reputed position with the literacy rate of 74.04 and 75.55 per cent respectively in 2011 yet inequality in the learning of male-female is a matter of concern for both entities. The figure for the district Mewat (which also lies at bottom in overall literacy as per ongoing census data) shows more discrimination in male-female learning, as here the male literacy rate is approximate to the double (69.97 per cent versus 36.60 per cent) of the females. To some extent, in areas like Mewat, Palwal and Fatehabad this discrimination is an outcome of societal stances, religion, fiscal or ethnical determinants and cultural stereotype as these factors of the environs have a direct or indirect association with literacy. So to ensure the equality and quality in education in basic or compulsory education, there is a need for massive investment on resources with communal awareness regarding significance as well as claptrap obstacles in the way of the learning.